The Effect of Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) to Return On Assets at KB Bukopin Bank year 2014-2023 - Putri Kusumawardhani, Aninditha (Dinasti International Journal of Management Science, 2024)
This study aims to determine the picture and influence from Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) on Return On Assets. This research object is a Bukopin KB Bank company on the Indonesia Stock Exchange period 2014-2023. The method used is the quantitative method with a descriptive approach and a verifikatif. The sample in this study were 30 financial reports of Bank KB Bukopin companies on the Indonesia Stock Exchange in the period 2014-2023, with the sample-making techniques, namely a saturated sample. The results of this study show that partially Capital Adequacy Ratio (CAR) has an effect on Return On Asset at a total of 71.5%, Non Performing Loan (NPL) has no effect on the Return On Asset at a 44.7% of its effect. Simultaneously, the results are obtained that Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) has an effect on the Return On Asset Company at the Bank KB Bukopin Stock Exchange for the period of 2014-2023 with the amount of 73,4%.